Removal of Mo(Vi), Pb(Ii), and Cu(Ii) from Wastewater Using Electrospun Cellulose Acetate/Chitosan Biopolymer Fibers - Pizarro-Konczak, J; Zapata-Ramirez, P; Gómez-Barrena, M; Lopez-Toro, E (Elsevier B.V., 2024)
Environmentally friendly polymers such as cellulose acetate (CA) and chitosan (CS) were used to obtain electrospun fibers for Cu2+, Pb2+, and Mo6+ capture. The solvents dichloromethane (DCM) and dimethylformamide (DMF) allowed the development of a surface area of 148 m2 g−1 for CA fibers and 113 m2 g−1 for cellulose acetate/chitosan (CA/CS) fibers. The fibers were characterized by IR-DRIFT, SEM, TEM, CO2 sorption isotherms at 273 K, Hg porosimetry, TGA, stress-strain tests, and XPS. The CA/CS fibers had a higher adsorption capacity than CA fibers without affecting their physicochemical properties. The capture capacity reached 102 mg g−1 for Cu2+, 49.3 mg g−1 for Pb2+, and 13.1 mg g−1 for Mo6+. Furthermore, optimal pH, adsorption times qt, and C0 were studied for the evaluation of kinetic models and adsorption isotherms. Finally, a proposal for adsorbate-adsorbent interactions is presented as a possible capture mechanism where, in the case of Mo6+, a computational study is presented. The results demonstrate the potential to evaluate the fibers in tailings wastewater from copper mining. © 2024 Elsevier B.V.